Entfesselte Körper Ästhetische Reflexionen zum modernen Menschen im frühen russischen Film - Wanner, Clea (Zürcher Filmstudien, 2023)
With its new media possibilities, film at the beginning of the 20th century brought increased intensity to the perception of body representations. It now showed the body in an aesthetic tension of authenticity, alienation, fetishization and ephemerality and at the same time created media and aesthetic constellations which combined numerous (theoretical) considerations and artistic articulations of a crisis-ridden modernity Visions of a new man - especially a new woman - were omnipresent. Using a broad spectrum of cinematic artefacts and historical materials, the book examines the first decade of narrative cinema, 1908-1918 in the late Tsarist Empire, how cinema specifically modeled cinematic concepts of physicality and thus significantly the idea of ​​the human being in Russian modernity, a cultural culture characterized by transmediality Epoch, co-designed. Accordingly, in the study, practices from theater and dance as well as cultural, artistic and literary discourses, such as from the avant-garde or symbolism, are intertwined with developments in film aesthetics and film theory.